THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF MOTHERS TOWARDS THEIR TODDLERS DENTAL HEALTH CARE - Ari Tri Wanodyo Handayani; Roedy Budirahardjo; Filky Nanda Mafilda (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Caries are one of the dental and oral health problems that are still the highest sequence today. The prevalence of caries in Indonesia gets 90% in the toddler population. A mother's knowledge about dental health will determine the mother's attitude towards children's dental health care, and low maternal knowledge is associated with high caries prevalence. The working area of the Bangsalsari Public Health Center is one of the areas in Jember that have a relatively high number of caries cases in toddlers, which is more than half of the number of toddlers experiencing caries. The study aims to analyse the relationship between knowledge and attitudes of mothers in the maintenance of dental health of toddlers in the work area of the Bangsalsari Public Health Center, Jember. Methods: This type of research is analytic observational with a cross-sectional approach. The research subjects were selected by a total sampling technique and obtained by as many as 126 mothers of toddlers. Data were collected using a knowledge and attitude questionnaire each containing 10 questions. The research data that have been obtained are then carried out with a nonparametric Spearman correlation test. Results: Spearman test shows a significant value of 0.000 (p<0.05), the correlation value obtained is r = 0.824 with a positive value. Conclusion: There is a significant relationship between knowledge and attitudes of mothers in dental health care for toddlers, and both variables have a unidirectional relationship with a very strong correlation level. Keywords : Attitudes of mothers, Dental health care, Knowledge, Toddlers